High iron-mediated increased oral fungal burden, oral-to-gut transmission, and changes to pathogenicity of Candida albicans in oropharyngeal candidiasis. Issue 1 (31st December 2022) - Tripathi, Aparna; Nahar, Anubhav; Sharma, Rishabh; Kanaskie, Trevor; Al-Hebshi, Nezar; Puri, Sumant
ABSTRACT: Background: Iron affects the diversity of the oral microbial landscape. Laboratory-strain CAI4 of Candida albicans that causes oropharyngeal candidiasis (OPC) exhibits iron-induced changes to the cell wall, impacting phagocytosis (by macrophages) and susceptibility of fungal cells to cell wall-perturbing antifungals, in vitro . Aim: To understand the effect of iron on the CAI4-strain, wild type (WT) SC5314-strain, and oral isolates of C. albicans . Methods: An immunosuppressed murine model of OPC was used to assess the effect of iron on oral-to-gut infection and antifungal susceptibility of the CAI4-strain. In vitro antifungal susceptibility, cell wall analysis, and phagocytic assays were performed under low and high iron, for the SC5314-strain and oral isolates. Results: High iron enhanced oral and gut fungal levels for the CAI4-strain in mice; CAI4 cells from low iron mice were more susceptible to antifungals. The SC5314-strain and oral isolates showed enhanced antifungal-resistance towards most antifungals tested, under high iron. Iron-mediated cell wall changes and phagocytic response in the SC5315-strain were similar to CAI4; oral isolates showed a variable response. Conclusion: Host iron can potentially alter infection severity and dissemination, efficacy of antifungal treatment, and host immune response during OPC. Clinical isolates showed most of these effects of iron, despite exhibiting a varied cell wall composition-change response to iron.